2019
DOI: 10.1111/jam.14350
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of yeasts from bovine rumen for potential use as probiotics

Abstract: Aims:The aim was to isolate, identify and characterize yeasts present in rumen fluid and to select strains showing potential as probiotics. Methods and Results: Rumen fluid was sampled from 4 herds of dairy and beef cattle and 77 yeast isolates were identified. Initial screening was based on the capacity to maintain viability in a medium with different ruminal conditions. A second screening in fresh rumen fluid to assess the growth of inoculated yeasts and evaluate in vitro neutral detergent fibre digestibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 29 publications
2
28
1
Order By: Relevance
“…These three yeast species identified in this study have also been reported in the ruminal micobiota analysis of cattle fed with tropical forages [3][4][5]. Pichia kudriavzevii was also the most frequent yeast in the rumen of cattle from South of Minas Gerais, Brazil, which may be due to its ability to better adapt to ruminal conditions.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…These three yeast species identified in this study have also been reported in the ruminal micobiota analysis of cattle fed with tropical forages [3][4][5]. Pichia kudriavzevii was also the most frequent yeast in the rumen of cattle from South of Minas Gerais, Brazil, which may be due to its ability to better adapt to ruminal conditions.…”
Section: Discussionsupporting
confidence: 74%
“…Pichia kudriavzevii was also the most frequent yeast in the rumen of cattle from South of Minas Gerais, Brazil, which may be due to its ability to better adapt to ruminal conditions. All strains of this species showed growth in anaerobic conditions and in temperatures that predominate in the rumen [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Candida pararugosa are ascomycetes first isolated from human feces in 1978 [1]. Later, it was found in vegetable food [2][3][4][5] and anatomic sites of animals and humans [6,7], where it is usually a harmless commensal organism and rarely involved in infections. A persistent detection of C. pararugosa from saliva of a two-year-old girl affected by rhabdomyosarcoma and relatives, and from the oral cavity of a healthy asymptomatic subject, was reported in 2004 [8,9].…”
Section: Introductionmentioning
confidence: 99%